Correction: A diet containing high- versus low-daidzein does not affect bone density and osteogenic gene expression in the obese Zucker rat model. Issue 12 (6th November 2019) - Rochester, Eric; Wickman, Brooke E.; Bell, Andrea; Simecka, Christy; Clayton, Zachary S.; Hakkak, Reza; Hooshmand, Shirin
Abstract : Correction for 'A diet containing high- versus low-daidzein does not affect bone density and osteogenic gene expression in the obese Zucker rat model' by Eric Rochester et al., Food Funct., 2019, 10, 6851–6857.